Analysis of cytokine induced phosphorylation of STAT3 in peripheral blood mononuclear cells by flow cytometric and western blot assays - Cromarty, Allan Duncan (University of Pretoria, 2014)
Dissertation (MSc)--University of Pretoria, 2013.